Independent and combined associations of VOCs exposure and MetS in the NHANES 2017–2020 - Xin Gao; Shanshan Xu; Na Lv; Chaokang Li; Ye Lv; Keyi Cheng; Hong Xu (Frontiers in Public Health)
IntroductionAs a worldwide public health concern, Metabolic syndrome (MetS) seriously endangers human health and life safety. It`s reported that there is a strong association between chemical pollutants and the development of MetS in recent years. Volatile organic compounds (VOCs), the primary emission pollutant in atmospheric pollutants, were closely associated with development of chronic diseases. However, the association between VOCs exposure and MetS is unclear. We aimed to investigate the association between VOCs and MetS and identify the behavioral patterns in which MetS patients may be exposed to VOCs.MethodsWe conducted a cross-sectional data analysis from 15,560 VOC-exposed participants in the NHANES. Multivariable logistic regression model, weighted quantile sum (WQS) regression model, and Bayesian kernel machine regression (BKMR) regression model were employed to explore chemical exposure`s independent and combined effects on MetS, respectively.ResultsA total of 2,531 individuals were included in our study, of whom 51.28% had MetS and 48.72% were non-MetS. The logistic regression model identified the association between N-acetyl-S-(N- methylcarbamoyl)-L-cysteine (AMCC), N-acetyl-S-(2-carboxyethyl)-L-cysteine (CEMA), N-acetyl-S-(2- cyanoethyl)-L- cysteine (CYMA) and MetS. In WQS regression analysis, the WQS index was significantly associated with AMCC, trans,trans-Muconic acid (t,t-MA), N-Acetyl-S-(1-cyano-2- hydroxyethyl)- L-cysteine (CYHA), CEMA, 2-Thioxothiazolidine-4-carboxylic acid (TTCA), N-acetyl- S-(3- hydroxypropyl-1-methyl)-L-cysteine (HPMM), CYMA, N-acetyl-S-(3,4-dihydroxybutyl)-L-cysteine (NADB), and N-Acetyl-S-(4-hydroxy-2-methyl-2-buten-1-yl)-L-cysteine (IPM3 cysteine). Finally, the combined association of MetS was positively associated with CEMA and CYMA in the BKMR regression model.DiscussionIn summary, we demonstrated that VOCs and their` metabolism were significantly associated with MetS. Compared results from these three models, CEMA and CYMA were identified as the factors associated with MetS. This study provides a research direction for the mechanism of VOCs that may induce the onset and development of MetS.